The Fungal Metabolites with Potential Antiplasmodial Activity - Yang, Bin; Huang, Jingxia; Zhou, Xuefeng; Lin, Xiuping; Liu, Juan; Liao, Shengrong; Wang, Junfeng; Liu, Feng-An; Tao, Huaming; Liu, Yonghong (Current medicinal chemistry, 2018)
Malaria caused by Plasmodium parasites is amongst many prevalent public health concerns in several tropical regions of the world. Nowadays, the parasite resistance patterns to most currently used drugs in therapy and insecticides have created an urgent need for new chemical entities exhibiting new modes of action and management strategies. Fungus has been proven to be an excellent source of biologically active compounds, which have been screened for antiplasmodial activity as potential sources of new antimalarial drugs. This review summarizes the current 255 natural products from fungus, which may possess antimalarial activity and can be classified as sesquiterpenes, diterpenes, sesterterpenes, alkaloids, peptides depsipeptides, xanthones, anthraquinones, anthrones, bioxanthracenes, bixanthones, preussomerins, depsidones, phenols, trichothecenes, azaphliones, macrolides, and steroids. However, the treatments available for malaria are limited. Thus, the identification of novel antimicrobial agents should be continued, and all possible strategies should be explored. Carrying forward the antimalarial screening in exited terrestrial and marine natural products library, and finding the new natural products in new resources, particularly those living in marine environments, are still important approaches to find new antimalarial agents. Unusual marine environments are associated with chemical diversity, leading to a resource of novel active substances for the development of bioactive products. Finding new antimalarial natural products in marine fungus, particularly those living in deep-sea and special marine environments, is an important approach to identify novel active agents.